Agricultural intensification impairs behavioral abilities and the expression of genes associated with social responsiveness in honeybees - Macri, Ivana Noelia; Moja, Pablo Joaquín; Latorre Estivalis, Jose M.; Cristos, Diego Sebastian; Zavala, Jorge Alberto; Farina, Walter Marcelo (Cell Press, 2024)
The honeybee Apis mellifera is one of the main pollinators in agroecosystems, and, consequently, its colonies are exposed to agrochemicals and more fragmented and homogeneous habitats. As a social insect, this could lead to an impairment of colony health and population growth. Here, behavioral, molecular, and toxicological approaches were performed in beehives located in an agricultural setting of the Argentine pampas to compare their global state at different times of crop management. Our results show that foraging bees were impaired in their sensory and cognitive abilities and the brain’s expression of several genes related to metabolic, immune, and neuronal processes associated with social behavior after crop flowering and pesticide application. These impairments suggest potential social consequences for pollinator colonies that inhabit these disturbed environments. To our knowledge, no previous study has reported the impaired effects of agricultural intensification on insect pollinators from an integrative neurobiological perspective under realistic field conditions.